Accommodation and disability-specific differences in nutritional status of children with disabilities in Kathmandu, Nepal: A cross-sectional study - Krishna Prasad Sapkota; Akira Shibanuma; Ken Ing Cherng Ong; Junko Kiriya; Masamine Jimba (BMC, 2023)
Abstract Background Worldwide, more than 150 million children < 18 years live with disabilities. These children are more vulnerable to malnutrition regardless of institutional care that they receive, such as daycare or residential care. In Nepal, little is known about the status of malnutrition and factors associated with malnutrition among children with disabilities. This study was conducted to investigate the factors associated with malnutrition based on the types of disability and accommodation. Methods This institution-based, cross-sectional study was conducted in 22 institutions in the Kathmandu Valley, Nepal. From these institutions, parents/guardians of all children with disabilities were recruited who were present there on the day of data collection. They were interviewed using a structured questionnaire. The questionnaire included questions on demographic characteristics, disability type and severity, accommodation place, feeding practices, and dietary patterns. The outcome variables, stunting, underweight, and obesity were measured using height-for-age, weight-for-age, and body mass index-for-age, respectively. A generalized linear model was used to investigate the factors associated with stunting and underweight, and multinomial logistic regression was used to identify the factors associated with overweight and obesity. Results Among the 345 children with disabilities, 45% were stunted, 33% were underweight, 19% were thin, and 12% were overweight. Children with physical disabilities (relative risk ratio = 1.88, 95% confidence interval [CI] = 1.26-2.81) were more likely to be stunted than those with sensory disabilities. Children with autism (adjusted odds ratio [aOR] = 5.56, 95% CI: 1.23-25.23) and intellectual disabilities (aOR = 5.84, 95% CI: 1.59-21.51) were more likely to be overweight and obese than those with sensory disabilities. No evidence was found regarding an association between accommodation type and malnutrition. Conclusion Children with disabilities are vulnerable to malnutrition in several ways. Different types of disabilities are associated with different forms of malnutrition. Considering the types of disabilities, tailor-made approaches should be adopted to improve malnutrition status.